KELAYAKAN USAHA BUDIDAYA SELADA ( Lactuca sativa L ) SISTIM POLYBAG - Ari Jumadi Kirnadi; Ana Zuraida; Ilhamiyah Ilhamiyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The research aimed to know lettuce production from the polybag cultivation system and the farming's business feasibility (R/C ratio). The research was conducted using the Action Method. Data collection is done by observation. To answer the purpose of knowing the production of lettuce using the polybag system, 200 polybags were used containing mixed media of soil, manure, and rice husk (2: 1: 1). Polybags are laid out with a spacing between polybags of 20 cm x 30 cm. The results showed that this study's average fresh weight of lettuce was 66.67 g per tree/polybag, so the total production of two hundred polybags produced 13.33 kg. or 2.2 tonnes per ha, is good enough. The polybag lettuce cultivation system is feasible because it has an R/C ratio value = 1.27.